Evaluation of high temperature performance of the Co-Cr-C coated P92 steel - Hoey, Thomas Michael (2017)
The motivation to increase the operation temperatures of fossil fuel power plant is primarily to improve power plant efficiency and reduce the negative environmental impact of fossil fuel power plant emissions. A main limitation to higher temperature operation is the enhanced oxidation damage of materials at increased temperatures. One of the most concerning areas of enhanced damage is on the inside surface of P92 ferritic steel (~ 9 % Cr) pipework which is used primarily to carry high temperature steam from the boiler. To combat the oxidation damage of P92 the energy industry has recently begun investigating the application of oxidation resistant coatings to P92 to enable higher temperature operation. Aluminium diffusion coatings have been the focus to date but they have been found to have a number of limitations, including coating degradation/porosity and a detrimental effect on the creep properties of the substrate, in part due to the high temperature coating process. Although other lower temperature coating methods, such as thermal spraying, have been considered these are limited by the practicalities and economics of spraying on the inside surface of P92 pipework. Therefore there is a real industrial need for consideration of a new coating type, for the inside of P92 pipework, which can be applied at low temperature and is also economical at full scale. This is where this thesis contributes by considering an electro-deposited Co-Cr-C coating never previously considered for this application. The Co-Cr-C type coating is electro-deposited to ~ 34-37 µm onto P92 ferritic steel. The coating is composed of ~ 35 wt % Cr3C2 electro-deposited within a cobalt matrix. The free-standing coating material and coated P92 system were subjected to isothermal oxidation in air and the oxidised state was characterised by a range of microstructural techniques. Oxidation behaviour, microstructural evolution and inter-diffusion between coating and substrate have all been considered. Thermo-Calc thermodynamic software has been used to make predictions about the long term evolution of the system. A series of uncoated and coated mechanical tests (creep, fatigue, creep-fatigue) have also been performed to assess the effect of coating application on the mechanical properties of P92 steel. This research has been motivated by industry at all stages and close collaboration has allowed for the most industrially relevant test conditions to be determined. Overall the Co-Cr-C coating is shown to be an industrially promising coating technology for application to P92. The study within this thesis shows that the good oxidation properties, interface behaviour and mechanical properties, combined with low temperature deposition and easy scale up, make this a viable coating for further development. It also has a number of advantages over the current aluminium coatings. The work within this thesis serves as a detailed feasibility and industry case study for further in-house testing by industrial sponsors, before future commercialisation of the product. A discussion of potential future work is also included at the end of the thesis.